The Influence of Aromatheraphy on the Client’s Anxiety Level Prior To Spinal Anesthesia Operative Procedure - Arwani Arwani; Iis Sriningsih; Rodhi Hartono (Jurnal Riset Kesehatan, 2013)
A quasy-experimental research with one group without control group design was applied to 40 samples who planned to be operated by a spinal anesthesia using the HRS-A (Hamilton Rating Scale for Anxiety). Data of the research was analyzed by using Wilcoxon rank signed. Research results showed that 40% samples experienced severe anxiety level before receiving aromatherapy, and 42.5% samples experienced moderate anxiety level after intervention. Statistical analysis showed that there was a significant effect of aromatherapy on the client’s anxiety level prior to spinal anesthesia operative procedure (p = 0.00). It is recommended to give lavender to clients before getting an operative procedure as a part of a standard operating procedure.